ACTG2-Associated Visceral Myopathy With Chronic Intestinal Pseudoobstruction, Intestinal Malrotation, Hypertrophic Pyloric Stenosis, Choledochal Cyst, and a Novel Missense Mutation. (February 2019) - Collins, Rebecca R. J.; Barth, Bradley; Megison, Stephen; Pfeifer, Cory M.; Rice, Luke M.; Harris, Samar; Timmons, Charles F.; Rakheja, Dinesh
Primary visceral myopathy caused by a pathogenic mutation in the gene encoding the enteric smooth muscle actin gamma 2 ( ACTG2 ) affects gastrointestinal and genitourinary tracts and often presents as chronic intestinal pseudoobstruction. We present a case of pediatric onset chronic intestinal pseudoobstruction associated with a novel missense ACTG2 mutation c.439G>T/p.G147C. In addition to the known disease manifestations of feeding intolerance and intestinal malrotation, our patient had a late-onset hypertrophic pyloric stenosis and a late-onset choledochal cyst, the former of which has not previously been described in patients with ACTG2 -associated visceral myopathy.